Life Table of Spodoptera exigua (Lepidoptera: Noctuidae) on Five Soybean Cultivars - Samira Farahani; Ali Asghar Talebi; Yaghoub Fathipour (Psyche: A Journal of Entomology)
Effect of five soybean cultivars (Sahar, JK, BP, Williams, and L17) on life table parameters of the beet armyworm Spodoptera exigua (Hübner) (Lepidoptera: Noctuidae) was evaluated at 25±1∘C, 60±5% relative humidity and a photoperiod of 16 h light/8 h dark. The highest and lowest net fecundity rates were obtained on Williams (244.1±19.4 eggs/female) and L17 (80.5±6.9 eggs/female), respectively. The net reproductive rates (𝑅𝑜) were highest on Williams (137.0±11.2 females/female/generation) and lowest on BP (41.3±4.1 females/female/generation). The intrinsic rate of increase (𝑟𝑚) differed significantly among five soybean cultivars, ranging from 0.1169 day−1 (on Williams) to 0.122 day−1 (on BP). The highest value of finite rate of increase (𝜆) was on Williams (1.18 day−1), which was significantly different from other cultivars. The mean generation time (𝑇𝑐) was significantly different on various cultivars, ranging from 32.0±0.3 days (on L17) to 28.8±0.3 days (on Sahar). The results are discussed with respect to the potential effect of soybean cultivars on the performance of S. exigua.